Assessing pharmacological interventions for bone metastases: the need for more patient-centered outcomes. Issue 3 (May 2012) - Ford, John A; Mowatt, Graham; Jones, Rob
Bone metastases are associated with a broad spectrum of clinical sequelae. Pain, reduced mobility, skeletal complications and treatment-related events reduce quality of life. Numerous randomized controlled trials have evaluated pharmacological interventions to treat bone metastases. The primary outcomes used have evolved over the past 25 years; from improvement in pain to time to first skeletal-related event (SRE). In the current definition, a SRE consists of pathological fracture, spinal cord compression or the need for radiotherapy or surgery to the bone. Currently used outcomes can detect small differences between interventions. However, there are several limitations to SRE-related outcomes. In this article we illustrate the evolution of outcomes used in randomized controlled trials, critically appraising current outcomes used and proposing that more patient-centered outcomes are needed.